TERMOELEKTRIK GENERATOR DAN FUNGSINYA - Gibran, Muhammad Alfian; Novianto, Sentot; Supriyadi, Supriyadi; Bhikuning, Annisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
This article summarizes and reviews various journals on the performance, applications, and development of Thermoelectric Generators (TEG) that convert temperature differences into electrical energy through the Seebeck effect. The aim of this review is to provide a comprehensive overview of advancements in TEG technology and its potential in enhancing energy efficiency and renewable energy utilization. The methodology includes a literature review of research methods applied in previous studies, including simulations and experiments aimed at improving TEG efficiency. Some studies also integrate TEG with phase change materials (PCM) to harvest energy from ambient temperature fluctuations. The review findings indicate that innovations in TEG materials and design can significantly improve the efficiency and sustainability of this technology. Additionally, this article discusses the applications of TEG in various fields, such as waste heat recovery from industrial processes and vehicles, as well as in wearable devices to harvest energy from body heat. A table presenting research methods and comparisons of previous studies is included to offer a thorough view of current developments in TEG technology. The conclusion of this review is that TEG has significant potential as a solution for waste heat recovery, wearable device applications, and as an efficient renewable energy source. The article also provides recommendations for future research, including the development of new materials and more optimal designs, to address existing challenges and maximize the potential of TEG.